Dendritic Cell-Targeted pH-Responsive Extracellular Vesicles for Anticancer Vaccination - Hyuk Lee; Hongsuk Park; Hyeong Sup Yu; Kun Na; Kyung Taek Oh; Eun Seong Lee (MDPI AG, 2019)
Immunotherapy can potentially treat cancers on a patient-dependent manner. Most of the efforts expended on anticancer vaccination parallel the efforts expended on prototypical immunization in infectious diseases. In this study, we designed and synthesized pH-responsive extracellular vesicles (EVs) coupled with hyaluronic acid (HA), 3-(diethylamino)propylamine (DEAP), monophosphoryl lipid A (MPLA), and mucin 1 peptide (MUC1), referred to as HDEA@EVAT. HDEA@EVAT potentiated the differentiation and maturation of monocytes into dendritic cells (DCs) and the priming of CD8+ T-cells for cancer therapy. MPLA and HA enabled HDEA@EVAT to interact with the toll-like receptor 4 and the CD44 receptor on DCs, followed by endosomal escape, owing to the protonation of pH-sensitive DEAP on the EV in conjunction with MUC1 release. The MUC1 was then processed and presented to DCs to activate CD8+ T-cells for additional anticancer-related immune reactions. Our findings support the anticancer vaccine activity by which HDEA@EVAT expedites the interaction between DCs and CD8+ T-cells by inducing DC-targeted maturation and by presenting the cancer-associated peptide MUC1.